A systemic fungicide might reduce the male genitalia of a stingless bee species by one-third - Ramos, Jenifer D.; Santos, Charles F.; Cristmann, Luisa; Blochtein, Betina (Entomological Communications, 2023)
Bees are essential pollinating insects that significantly contribute to crop production. However, the use of pesticides in modern agriculture has resulted in bees being exposed to a plethora of harmful substances. Larvae of bees are particularly susceptible to exposure, as they can consume contaminated larval food during development. This study opportunely examined the effects of fungicides and insecticides on the size and shape of the genitalia of Scaptotrigona bipunctata (Lepeletier, 1836) males (Hymenoptera: Apidae: Meliponini) during larval development when experimental design was structured to obtain female bees (workers). Therefore, the geometric morphometric analyses were based on male bees that opportunistically emerged. Our findings showed a significant difference in the size of the genitalia of S. bipunctata males exposed to a systemic fungicide during larval development, while the genital shape remained similar. Although the exact impact of these morphological changes on the reproductive success of S. bipunctata males is uncertain, they suggest an adverse effect of pesticides on bees.